The promotion effect of uniaxial strain on hydrogen aggregation in tungsten - Ma, Fang-Fei; Li, Yu-Hao; Ren, Qing-Yuan; Zhou, Hong-Bo; Lu, Guang-Hong (Frontiers in Materials, 2023)
The aggregation behavior of hydrogen (H) isotopes after low-energy plasma irradiation is particularly important for tungsten (W) in future fusion devices. Here, using the first-principles calculation, we demonstrated an interesting strain effect that may drive the planar aggregation of interstitial H atoms in W. Although there are attractive interactions between H atoms, the spontaneous nucleation of these platelet-like H clusters in strain-free W appears impossible even at high H concentrations (up to 0.1 at.%) because of the extremely low configurational entropy. However, applied uniaxial strain significantly increased the binding energy of H platelets and enabled planar H clusters to form. These results suggest that uniaxial strain enhances the nucleation and growth of H platelets in W, regardless of whether it is a compressive or tensile strain. Moreover, the binding energy of one-layer H clusters was lower than that of parallel H platelets, implying that the formation of multi-layer H clusters in W and their stability is also promoted by uniaxial strain. Meanwhile, the presence of planar H clusters dramatically reduced the vacancy formation energy in W, which in turn provided an extra trapping site to accommodate excessive H atoms. These results provide an important reference for understanding the H evolution in W-PFMs.